2012
DOI: 10.1113/jphysiol.2012.230409
|View full text |Cite
|
Sign up to set email alerts
|

Colour and pattern selectivity of receptive fields in superior colliculus of marmoset monkeys

Abstract: Key points• In addition to supplying signals for conscious visual perception, the pathways from eye to brain serve visual functions such as reflex eye movements, which are controlled by a brain area called the superior colliculus (SC).• It is known that short-wavelength sensitive (S or 'blue') cone photoreceptors serve an evolutionary ancient pathway for colour vision but whether S cones also contribute to reflex eye movements is poorly understood.• We show that in recordings from anaesthetised marmoset monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 70 publications
(142 reference statements)
5
26
0
Order By: Relevance
“…Of course, at near-foveal eccentricities, where higher resolution vision dominates, band-pass tuning curves were observed, but the overwhelming population result was low-pass, unlike in V1. In anesthetized marmosets, band-pass SC tuning was suggested 52 , although it is not clear how this may have depended on eccentricity in that study. These authors also observed low-pass tuning in some of their neurons like in our case.…”
Section: Discussionmentioning
confidence: 72%
“…Of course, at near-foveal eccentricities, where higher resolution vision dominates, band-pass tuning curves were observed, but the overwhelming population result was low-pass, unlike in V1. In anesthetized marmosets, band-pass SC tuning was suggested 52 , although it is not clear how this may have depended on eccentricity in that study. These authors also observed low-pass tuning in some of their neurons like in our case.…”
Section: Discussionmentioning
confidence: 72%
“…Those sensory units are most likely in the visual cortex, where neurons are tuned for orientation, adapt selectively to stimuli like ours, and correlate strongly with perception (Fang et al 2005;Kohn 2007;Ress and Heeger 2003). Orientationspecific adaptation has not been found in subcortical neurons (Solomon et al 2004), and neurons in the superior colliculus have little if any orientation selectivity (White and Munoz 2012, but see Tailby et al 2012). Orientation tuning is weak in the human lateral geniculate nucleus (Ling et al 2015) and primate retinal ganglion cells (Passaglia et al 2002;Schall et al 1986) and most apparent for orientations that are cardinal or radial to the fovea, which our stimuli were not.…”
Section: Experiments 2 and 3: Orientation-specific Adaptationmentioning
confidence: 99%
“…Anatomically, retinal inputs to K layers do not show the strict eye segregation that defines the P and M layers [16]. Additionally, subcortical inputs to dLGN from the superior colliculus and the parabigeminal nucleus selectively target K layers [17,18], and many neurons in those areas show binocular excitatory convergence [19][20][21]. Corticofugal axons likely carry binocular signals, but they make synapses in all layers of the dLGN and therefore should influence P cells and M cells as well as K cells.…”
Section: Sources Of Binocular Inputs To K Cellsmentioning
confidence: 99%